Quality of Customer Service: Service Satisfaction as a Key at KCP Bank Sumut Syariah: - Hotma Rizky Putri Lubis; Sarinah br. Hasibuan; Kanaya Tri Nazwa; Sari Wulandari; Muhammad Rahmat (SEAN Institute, 2025)
This study aims to analyze the quality of Customer Service (CS) at KCP Bank Sumut Syariah and its impact on customer satisfaction levels. In this study, the author uses a quantitative approach with a survey method to collect data from respondents consisting of KCP Bank Sumut Syariah customers. The data obtained were then analyzed using descriptive and inferential statistical analysis techniques to see the relationship between service quality and customer satisfaction. The results of the study indicate that the quality of Customer Service at Bank Sumut Syariah plays a significant role in increasing customer satisfaction. The three main aspects that influence are speed of service, friendliness of CS, and accuracy in providing information. Although most customers expressed satisfaction with the services provided, there were still some complaints about the response time which was considered slow and the unclear information provided in some cases. Therefore, efforts to improve service quality such as routine training and utilization of information technology are needed to minimize the gap between expectations and reality felt by customers. The conclusion that can be drawn is that optimal Customer Service quality can increase customer satisfaction and build long-term loyalty. For that, Bank Sumut Syariah needs to continue to make improvements and innovations in service, both in terms of improving the quality of human resources through training and utilizing technology to speed up the service process. Strengthening an organizational culture that is oriented towards customer satisfaction is also very important to support continuous improvement in service quality.